Python aplicado em planejamento fatorial em química - Souza, André Luiz Machado Simão de (2022)
The scope of this course conclusion work involves the application of a new tool for factorial planning for the optimization of experiments using the Python programming language, where the author adapted and compiled three routines of the free program Octave in a library named “pde.py”. To illustrate the use of the tool, the four examples discussed in the article published by the journal Química Nova were reproduced, in which the application of the programming routine in complete (1), fractional (2), Doehlert type (3) factorial planning is approached and discussed. and Box-Behnken (4). The purpose of the work is to present in stages the procedures performed in each example with this new tool, in this way 63 videos were prepared that help the reader throughout the development of the content addressed